2004
DOI: 10.1103/physreve.70.046310
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear theory of a “shear-current” effect and mean-field magnetic dynamos

Abstract: The nonlinear theory of a "shear-current" effect in a nonrotating and nonhelical homogeneous turbulence with an imposed mean velocity shear is developed. The shear-current effect is associated with the W x J term in the mean electromotive force and causes the generation of the mean magnetic field even in a nonrotating and nonhelical homogeneous turbulence (where W is the mean vorticity and J is the mean electric current). It is found that there is no quenching of the nonlinear shear-current effect contrary to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
183
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(197 citation statements)
references
References 32 publications
(76 reference statements)
14
183
0
Order By: Relevance
“…(17)- (19), the termsN f , N h , andN g are determined by the third moments appearing due to the nonlinear terms; the source terms I f i j , I h i j , and I g i j , which contain the large-scale spatial derivatives of the mean magnetic and velocity fields, are given by Eqs. (A3)-(A6) in Rogachevskii & Kleeorin (2004). These terms determine turbulent magnetic diffusion and effects of nonuniform mean velocity on the mean electromotive force.…”
Section: Equations For the Second Momentsmentioning
confidence: 99%
See 3 more Smart Citations
“…(17)- (19), the termsN f , N h , andN g are determined by the third moments appearing due to the nonlinear terms; the source terms I f i j , I h i j , and I g i j , which contain the large-scale spatial derivatives of the mean magnetic and velocity fields, are given by Eqs. (A3)-(A6) in Rogachevskii & Kleeorin (2004). These terms determine turbulent magnetic diffusion and effects of nonuniform mean velocity on the mean electromotive force.…”
Section: Equations For the Second Momentsmentioning
confidence: 99%
“…(17)- (19) we use an approach that is similar to that applied in Rogachevskii & Kleeorin (2004). We take into account that in Eq.…”
Section: Equations For the Second Momentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, recent studies have shown that mean-field dynamo action is possible due to non-helical turbulence and shear (Brandenburg 2005a;Yousef et al 2008a,b;Brandenburg et al 2008). The nature of this dynamo is not yet entirely clear and may be attributed to the so called shear-current effect (Rogachevskii & Kleeorin 2003, 2004 or to the incoherent (stochastic) α-effect (Vishniac & Brandenburg 1997). According to Brandenburg et al (2008) the latter explanation is consistent with the turbulent transport coefficients.…”
Section: Introductionmentioning
confidence: 99%